Stem cells to replace or regenerate the diabetic pancreas: Huge potential & existing hurdles - Bhartiya, Deepa (Indian J Med Res, 2016)
Various stem cell sources are being explored to treat diabetes since the proof-of-concept for cell therapy was laid down by transplanting cadaveric islets as a part of Edmonton protocol in 2000. Human embryonic stem (hES) cells derived pancreatic progenitors have got US-FDA approval to be used in clinical trials to treat type 1 diabetes mellitus (T1DM). However, these progenitors more closely resemble their foetal counterparts and thus whether they will provide long-term regeneration of adult human pancreas remains to be demonstrated. In addition to lifestyle changes and administration of insulin sensitizers, regeneration of islets from endogenous pancreatic stem cells may benefit T2DM patients. The true identity of pancreatic stem cells, whether these exist or not, whether regeneration involves reduplication of existing islets or ductal epithelial cells transdifferentiate, remains a highly controversial area. We have recently demonstrated that a novel population of very small embryonic-like stem cells (VSELs) is involved during regeneration of adult mouse pancreas after partial-pancreatectomy. VSELs (pluripotent stem cells in adult organs) should be appreciated as an alternative for regenerative medicine as these are autologous (thus immune rejection issues do not exist) with no associated risk of teratoma formation. T2DM is a result of VSELs dysfunction with age and uncontrolled proliferation of VSELs possibly results in pancreatic cancer. Extensive brainstorming and financial support are required to exploit the potential of endogenous VSELs to regenerate the pancreas in a patient with diabetes.